2023
DOI: 10.1186/s12302-023-00712-9
|View full text |Cite
|
Sign up to set email alerts
|

Potassium citrate-derived porous carbon with high CO2 capture and Congo red adsorption performance

Abstract: The objective is to achieve the goal of carbon neutrality, controlling CO2 emissions is a primary problem to be solved in the current environmental protection field. Eliminating the environmental pollution of dyes in industrial wastewater is also an urgent problem to be solved in the field of environmental protection. The adsorption technique is an effective way to deal with these two issues. Developing high-efficiency adsorbents is an essential work in the adsorption field. In this work, a simple carbonizatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…As shown in Figure 3 (a), PC-700, PC-800, and PC-900 showed typical type-I isotherms, indicating the presence of micropores in their structures. 30 At a low relative pressure ( P / P 0 < 0.05), the N 2 isotherm exhibited a sharp increase, which meant abundant micropores in the carbon material. Besides, compared with PC-700 and PC-800, PC-900 showed a higher N 2 adsorption capacity, which meant that there were more microporous structures in PC-900.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure 3 (a), PC-700, PC-800, and PC-900 showed typical type-I isotherms, indicating the presence of micropores in their structures. 30 At a low relative pressure ( P / P 0 < 0.05), the N 2 isotherm exhibited a sharp increase, which meant abundant micropores in the carbon material. Besides, compared with PC-700 and PC-800, PC-900 showed a higher N 2 adsorption capacity, which meant that there were more microporous structures in PC-900.…”
Section: Resultsmentioning
confidence: 99%
“…The specific surface area and the pore structures of the prepared porous carbon materials were tested by the N 2 adsorption/desorption method. As shown in Figure (a), PC-700, PC-800, and PC-900 showed typical type-I isotherms, indicating the presence of micropores in their structures . At a low relative pressure ( P / P 0 < 0.05), the N 2 isotherm exhibited a sharp increase, which meant abundant micropores in the carbon material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that this catalyst is highly efficient, environmentally friendly and low-cost compared to other catalysts. Wang et al 12 derived porous carbon from potassium citrate for CO 2 capture and dye adsorption applications. In pyrolysis, the catalyst drives the rate of cracking, which results in a rapid increase in gas production with decreased liquid oil.…”
Section: Introductionmentioning
confidence: 99%
“…[16,17] It could not only increase economic benefits but also reduce environmental pollution. [18] At the moment, porous materials made from biomass and other materials were getting more attention, for instance, porous carbon materials made from potassium citrate, [19] nitrogen-doped hierarchical porous carbon generated from silkworm cocoon waste as reliable electrode materials for effective capacitive desalination, [20] by utilizing the sodium polyacrylate in applied diaper waste, pyrolysis can be exploited to create porous material, [21] porous carbon obtained from cattail grass as a high-capacity anode material, [22] the wetimpregnation and calcination approach was employed to manufacture the heterogeneous magnetic catalyst for the synthesis of biodiesel using waste diapers as the raw material. [23] As major by-product of soybean processing industries, soybean hulls residue (SHR) is a kind of typical natural polymer waste.…”
Section: Introductionmentioning
confidence: 99%